(untitled) (Bulletin of criminological association of Ukraine, 2023)
Attention is focused on the fact that the legal regulation of the provision of territorial defense of Ukraine by local self-government bodies is a regulatory and structuring influence on social relations carried out with the help of legal norms that arise in the sphere of forming conditions and guarantees for the most effective and complete implementation of socially and nationally important measures with territorial defense of Ukraine. It has been found that the legal regulation of the provision of territorial defense of Ukraine by local self-government bodies consists of a large group of normative and legal acts, which include the Constitution of Ukraine, as well as international, legislative and by-law normative documents. It is emphasized that normative legal acts, the norms of which are aimed at regulating social relations in the researched area, are most expediently divided into: a) general ones that determine the status, powers and functions of local self-government, the order and peculiarities of the functioning of its components, etc.; b) special normative acts, which reveal the content of activities and powers directly in the direction of ensuring territorial defense. It is noted that in the system of regulation of territorial defense of Ukraine by local self-government bodies, a key place is assigned to the norms of the administrative field of law, because it is with their help: a) the legal status of local self-government bodies is determined in general, and in the context of the implementation of territorial defense, in particular; b) administrative procedures for ensuring the territorial defense of Ukraine by local self-government bodies are revealed; c) administrative forms and methods of carrying out the relevant activities are established; d) the boundaries and directions of the investigated support are established.